Interactive learning technologies at theoretical foreign language classes - Alla Paladieva, Irina Biletskaya (Opción, 2019)
The purpose of this research is to explore interactive foreign language learning technologies. In order to achieve this goal, the study used a set of methods relevant to the problem at hand: analysis and synthesis of psychological, pedagogical, scientific, and methodological literature. As a result, use of interactive learning methods while studying the foreign language significantly increases the interest and motivation of students and improves their knowledge in the subject area. As a conclusion, interactive educational technologies help students learn the material through their own experience.